2023
DOI: 10.1177/10815589221149186
|View full text |Cite
|
Sign up to set email alerts
|

Effect of renal function on the prognostic importance of chloride in patients with heart failure

Abstract: Hypochloremia has recently gained interest as a potential marker of outcomes in patients with heart failure (HF). The exact pathophysiologic mechanism linking hypochloremia to HF is unclear but is thought to be mediated by chloride-sensitive proteins and channels located in kidneys. This analysis aimed to understand whether renal dysfunction (RD) affects the association of hypochloremia with mortality in patients with HF. Using data from a nationwide registry, 438 cases with complete data on serum chloride con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 33 publications
0
4
0
3
Order By: Relevance
“…Our study is consistent with and extends the results of previous epidemiological studies highlighting the independent association of lower serum chloride levels with an increased long-term risk of adverse clinical outcomes in heart failure, irrespective of ejection fraction. [5][6][7][8][9][10][24][25][26][27][28][29][30][31][32][33] In particular, LVEF spanned across all categories, and the prognostic role of chloride was not modified by LVEF in the meta-regression analysis.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Our study is consistent with and extends the results of previous epidemiological studies highlighting the independent association of lower serum chloride levels with an increased long-term risk of adverse clinical outcomes in heart failure, irrespective of ejection fraction. [5][6][7][8][9][10][24][25][26][27][28][29][30][31][32][33] In particular, LVEF spanned across all categories, and the prognostic role of chloride was not modified by LVEF in the meta-regression analysis.…”
Section: Resultsmentioning
confidence: 94%
“…The study with the largest population included 4762 patients 24 whereas the smallest study included 161 patients. 25 Among the included studies, seven reported hazard ratio per unit change of serum chloride for eight patient cohorts, [6][7][8][26][27][28][29] five studies reported hazard ratio comparing hypochloremia and normochloremia for eight cohorts of patients, 5,24,25,30,31 and three studies reported both types of hazard ratio assessments. 10,32,33 Six studies included patients with acute heart failure, 6,8,10,26,29,31 seven studies included patients with chronic hazard ratios 5,7,24,27,28,32,33 and the remaining two studies included a mixed population of patients with acute and chronic heart failure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations